Seismic Behavior of Steel Off-Diagonal Bracing System (ODBS) Utilized in Reinforced Concrete Frame. (10th July 2014) - Ramin, Keyvan
Abstract : The introduction of an eccentricity in this system results in a geometric nonlinearity behavior. The midpoint of the diagonal member is connected to the corner joint using a brace member with a relatively low stiffness, thus forming a three-member bracing system in each braced panel. An iterative method of analysis has been developed to study the nonlinear load-deflection behavior of ODBS. The results indicate that the load-deflection behavior of this system follows a nonlinear stiffness-hardening pattern with two yielding points, which reflect the tensile failure of different bracings; the present study aims to investigate the efficiency of applying off-diagonal steel braces to reinforced concrete frames. To achieve this, three types of 2-story, 6-story, and 15-story structures without and with X-bracing and off-center bracing systems were modeled using SAP2000 software, and for micromodeling ANSYS software was used to achieve finite element results for an exact comparison between various retrofitting systems. The results showed that the structures strengthened by toggle bracing system revealed better behavior for low oscillation periods. Moreover, this type of bracing system is quite suitable for 10-story structures but not for higher ones. Its main problem, which requires special contrivances to solve, is the existence of a soft ground floor.